Upaya Advokasi Non Kekerasan Bds Movement Indonesia dalam Merespon Agresi Militer Israel di Gaza (2023-2024) - Aswar, Hasbi; Anggraini, Dea Nabilla (The Indonesian Islamic Studies and International Relations Association (Insiera), 2026)
Israel's aggression against Palestinians, which culminated in Israel's military aggression in Gaza in 2023-2024, has provoked a broad response from the international community, including the emergence of various global solidarity movements such as the BDS movement Indonesia . This study aims to explain the efforts of the Indonesian BDS Movement in conducting non-violent advocacy to respond to the aggression through peaceful protest strategies and boycott campaigns against entities affiliated with Israel. This study uses Jørgen Johansen's theory of non-violence, which divides peaceful action into four main categories: nonviolent protest, non-cooperation, nonviolent intervention, and civil disobedience. This research argues that the strategy of the Indonesian BDS Movement reflects two main forms, namely peaceful protest and refusal to cooperate with those who support Israeli colonialism. The results show that BDS movement Indonesia consistently carries out advocacy through peaceful demonstrations, digital campaigns, online petitions, and collaborations with humanitarian organizations. These findings confirm that the non-violent approach used is effective in strengthening public solidarity, building social awareness of humanitarian issues in Gaza, and demonstrating the role of Indonesian civil society in fighting for justice and human rights for the Palestinian people.